The Influence of Participation in Budgeting, Budget Evaluation, and Accountability Accounting on Managerial Performance in Regional Apparatus Organizations (Opd) Deli Serdang Regency - Intan Wahyuni Nasution; Erlina; Keulana Erwin (Institute of Computer Science (IOCS), 2022)
This study aims to examine and analyze the effect of Budgeting Participation, Budget Evaluation, and Accountability Accounting on the Managerial Performance of Regional Apparatus Organizations (OPD) Deli Serdang Regency. The type of research used is causal research. The population in this study is the manager of the work unit or structural officials at the Deli Serdang Regency Government's Regional Apparatus Organization Work Unit, amounting to 124 people from 31 OPD. The data in this study are primary data and data collection techniques using questionnaires. The data analysis method used in this research is structural equation modeling-partial least square (SEM-PLS) using SmartPLS software. The results of this study indicate that Participation in Budgeting, Budget Evaluation, and Accountability Accountability each has a significant positive effect on the Managerial Performance of Regional Apparatus Organizations (OPD) Deli Serdang Regency. This means that if Participation in Budgeting, Budgeting Evaluation, and Accountability is increased, it will improve managerial performance.